Reinventing Grammar Pedagogy through Mobile-Assisted Learning: Busuu-Assisted Tense Mastery in an Indonesian Madrasah Tsanawiyah - Sepia Sepia; Kalsum Kalsum; Abdul Haris Sunubi; Munawir Munawir (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This research addresses the persistent challenge of tense instruction in Indonesian madrasah tsanawiyah, where grammar learning is often perceived as rule-heavy and detached from meaningful practice. The study aims to examine the extent to which Busuu-assisted learning can enhance eighth-grade students’ English tense mastery and to outline a feasible classroom integration model within a realistic school timetable. A pre-experimental one-group pre-test–post-test design was employed with qualitative approach. The participants were 23 eighth-grade students at MTs DDI Tuppu Pinrang selected from an intact class; however, complete matched pre- and post-test scores were available for 22 students and were used for analysis. Students completed a 30-item multiple-choice grammar test on simple present, simple past, and simple future tenses before and after six weekly Busuu-assisted treatments (two class periods per meeting). Data were analyzed using descriptive statistics and a paired comparison, applying the Wilcoxon signed-rank test due to non-normal gain scores. The results showed a substantial increase in students’ tense mastery from pre-test (M = 20.18) to post-test (M = 28.23), with a significant pre–post difference (p < .001) and a very large effect (r ≈ 0.88). The findings suggest that structured mobile-assisted practice through Busuu, combined with teacher guidance and error-focused review, can serve as a practical strategy for revitalizing grammar pedagogy in Islamic junior high school contexts.